OPTIMALISASI PEMBERDAYAAN KEMAMPUAN PT. DIRGANTARA INDONESIA GUNA MENINGKATKAN KESIAPAN ALUTSISTA TNI ANGKATAN UDARA - Angki Rizki Pandu; Achmad Faisol (STMIK Mardira Indonesia, Bandung, 2022)
In order to maintain the sovereignty and stability of the State of Indonesia, Indonesia must build a reliable national defense force. One of the requirements in building a national defense force that must be met by the Indonesian Armed Force is the availability of defense equipment that is in accordance with the operational needs of the Indonesian Armed Force. Indonesian Air Force as the guardian of sovereignty in the air, the defense equipment must always be updated and maintained properly. With the limited defense budget allocated by the government to the Indonesian Air Force, Indonesian Air Force is trying to meet the needs of defense equipment by empowering the domestic defense industry, in this case Indonesian Aerospace Industry as the only aerospace industry in the country. The problem that exists today is Indonesian Aerospace Industry has not been optimally empowered in increasing the readiness of the Indonesian Air Force defense equipment. With the increasing need and readiness of defense equipment as well as to avoid the dependence of the Indonesian Air Force on foreign defense equipment products in an effort to meet and maintain defense equipment readiness, it is necessary to have cooperation between the Indonesian Air Force and Indonesian Aerospace Industry. Empowerment of Indonesian Aerospace Industry can be achieved if there is a real effort in realizing the resolution of existing problems by reviewing the institutional and management levels of cooperation, integrating technological research capabilities between the Indonesian Air Force and Indonesian Aerospace Industry, and synergize existing resources. If these efforts can be realized then the empowerment of Indonesian Aerospace Industry in increasing the readiness of the Indonesian Air Force defense equipment can be realized so that the stability of the Indonesian State can be maintained. Keywords: optimization, capability, readiness of defense equipment